2006
DOI: 10.1017/s0959774306000060
|View full text |Cite
|
Sign up to set email alerts
|

The Singing Neanderthals: the Origins of Music, Language, Mind and Body, by Steven Mithen. London: Weidenfeld & Nicholson, 2005. ISBN 0-297-64317-7 hardback £20 & US$25.2; ix+374 pp.

Abstract: Why are humans musical? Why do people in all cultures sing or play instruments? Why do we appear to have specialized neurological apparatus for hearing and interpreting music as distinct from other sounds? And how does our musicality relate to language and to our evolutionary history?Anthropologists and archaeologists have paid little attention to the origin of music and musicality — far less than for either language or ‘art’. While art has been seen as an index of cognitive complexity and language as an essen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
127
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(146 citation statements)
references
References 21 publications
3
127
0
Order By: Relevance
“…Darwin [37] suggested that early progenitors of man used their voices primarily in singing during courtship, incorporating in their song imitations of natural sounds. More recent authors have adopted this suggestion of a musical protolanguage [36,38], and Fitch has argued that sexual selection would have been responsible for the elaboration of such a protolanguage [36]. If so, sexual selection for more elaborate vocalizations would explain the origin of vocal learning in hominids just as has been proposed for birds.…”
Section: Advantages Of Vocal Learning In Humansmentioning
confidence: 99%
“…Darwin [37] suggested that early progenitors of man used their voices primarily in singing during courtship, incorporating in their song imitations of natural sounds. More recent authors have adopted this suggestion of a musical protolanguage [36,38], and Fitch has argued that sexual selection would have been responsible for the elaboration of such a protolanguage [36]. If so, sexual selection for more elaborate vocalizations would explain the origin of vocal learning in hominids just as has been proposed for birds.…”
Section: Advantages Of Vocal Learning In Humansmentioning
confidence: 99%
“…"While the concept of music may vary, all cultures have song and dance, and make some form of internal repetition and variation in their musical utterances; they use rhythmic structures based on distinctions between note lengths and dynamic stresses" (Mithen, 2005, p.12 quoting Nettl, 1983. Much has been written about what are described as cultural and musical "universals", but are there actually such universals?…”
Section: What Is Music and How Does It Influence Behaviour?mentioning
confidence: 99%
“…Both music and language have the quality of expressive phrasing (Mithen, 2005, p.24, quoting Brown, 2000. The cognitive demands of music may be fewer than those of language.…”
Section: Emotion and Moodmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Some support from these views comes from the work of Mithen, who has argued that spoken language and music evolved from a proto-language, a musi-language which evolved from primate calls used by the Neanderthals: it was emotional but without words as we know them. 7 The link between music and emotion seems to be accepted for all time. 8 Plato considered that music played in different modes would arouse different emotions, and as a generality most of us would agree on the emotional significance of any particular piece of music, whether it is happy or sad, for example.…”
Section: Music and Affectmentioning
confidence: 99%